ANALISIS DAMPAK MODEL PEMBELAJARAN SENTRA TERHADAP ASPEK PERKEMBANGAN ANAK DALAM KURIKULUM 2013 DI TK-KB AL-HIJRAH - Agnes Purba; Nurkhalisah; Wahyu Windari; Lupia Subaidah; Sri Indriani Harianja; Winda Sherly Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The center-based learning model is an educational approach that integrates play elements into the teaching and learning process to foster effective and engaging learning for children. This study employs a qualitative approach with a case study design to analyze the impact of the center-based learning model on children's development within the 2013 curriculum at TK-KB Al-Hijrah. Data collection methods include observation, interviews, and document analysis. The results show that the implementation of the center-based learning model in the 2013 early childhood education curriculum has a positive impact on various aspects of children's development. Children demonstrated significant improvement in cognitive, socio-emotional, physical-motor, moral, language, and artistic skills. This study suggests that educators and policymakers should adopt and develop the center-based learning model in kindergartens.